A Study of the Promotion of Convergence in the Calculation of Complex Chemical Plants - Orbach, Oded (My University, 1969)
Techniques for accelerating the convergence of multi-variable iterative calculations were studied. The study is mainly concerned with iterations which result from the calculation of recycle processes of complex chemical plants. The conditions for convergence and the existence of the solution of linear and non-linear iterations were obtained. Special attention was given to the asymptotic behaviour of the iterations since, in most cases, they approach geometric progression. The convergence of an Alkylation unit simulation was studied by implementation of the "full matrix" technique for accelerating the rate of convergence. The geometric extrapolation technique was described and applied successfully for accelerating the convergence of the calculation of multi-component distillation columns.
This thesis is missing page 147 in all printed copies. - Digitization Centre
Keywords: convergence; complex chemical plant